Benedetta and the creation of ‘Second Futurism’ - Larkin, Erin (Journal of Modern Italian Studies, 2013)
Despite the recent vogue in studies on Futurism, writer and artist Benedetta Cappa Marinetti has received little critical attention. Few scholarly works have focused on her essays regarding woman and the Fascist state, and in particular the role of mother. It has been argued that these texts support not only the position that women futurists - in adhering to a movement remembered for its disprezzo della donna - were victims of their self-accepting inferiority, but also the view that Futurist attitudes towardswomen were a precursor of Fascist-era gender politics. Larkin challenges this position, and discusses crucial new archival research, which reveals how maternity in Benedetta's works is actually linked to her radical new reformulation of Futurism. Far from seconding woman's inferior position within the avant-garde, or indeed the Fascist state, Benedetta uses the issue of maternity subtly to subvert her status - in both the movement and society - from within. © 2013 Taylor & Francis.
Keywords: Avant-garde; Benedetta; Cappa; Futurism; Marinetti; Women writers; dept.wll